169k views
5 votes
F(x) = 2^3x-1 - 2find the inverse function of f(x)

F(x) = 2^3x-1 - 2find the inverse function of f(x)-example-1
User Totonga
by
6.1k points

1 Answer

5 votes

Given the function


f(x)=2^(3-x)-2

Substitute y = f(x) into the function above


y=2^(3-x)-2

Make 'x' the subject of the formula


y+2=2^(3-x)

Take the logâ‚‚ of both sides


\begin{gathered} \log _2(y+2)=\log _22^((3-x)) \\ \log _2(y+2)=3-x\log _22 \\ \end{gathered}

Note:


\log _22=1

Therefore,


\begin{gathered} \log _2(y+2)=(3-x)*1 \\ \log _2(y+2)=3-x \end{gathered}

Isolating 'x'


x=3-\log _2(y+2)

Replace 'x' with 'y'


y=3-\log _2(x+2)

Hence,


f^(-1)(x)=3-\log _2(x+2)

The correct option is Option 2.

User AlanFoster
by
5.8k points